Prevalence and factors associated with Chinese herbal medicine use among middle-aged and older Chinese adults with diabetes mellitus - Chen, Yanting; Lin, Leying; Sun, Shanwei; Cui, Kaiwang; Wu, Qingrong (Frontiers in Pharmacology, 2025)
BackgroundThe effectiveness of traditional Chinese medicine (TCM) in treating diabetes has been confirmed in China and globally. However, research on the use of Chinese herbal medicine (CHM) among middle-aged and elderly patients with diabetes and its associated factors is limited. This study aims to explore the prevalence of CHM use among these patients and its associated factors.MethodsThis study utilized data from the China Health and Retirement Longitudinal Study, which covers Chinese adults aged ≥45 years. A cross-sectional analysis was conducted on 3,347 participants who used CHM for diabetes treatment. Multivariate logistic regression models were employed to identify key factors (including demographic characteristics, health status, and healthcare utilization) that predict CHM use among patients with diabetes.ResultsThe prevalence of CHM use for diabetes was 10.8% among middle-aged and older Chinese patients with diabetes. Compared to patients with diabetes who did not use CHM, those who did were more likely to be older (OR = 1.31; 95% CI = 1.04, 1.65), visit TCM hospitals (OR = 1.24; 95% CI = 1.01, 1.53), engage in self-treatment (OR = 1.90; 95% CI = 1.38, 2.61), have kidney disease (OR = 1.50; 95% CI = 1.05, 2.14), and have asthma (OR = 2.19; 95% CI = 1.29, 3.70). In the combined effect analysis, patients with both kidney disease and asthma were most likely to use CHM (OR = 4.20; 95% CI = 1.93, 9.14).ConclusionThe prevalence of CHM use among middle-aged and elderly Chinese patients with diabetes was relatively low, and was associated with specific health conditions and healthcare behaviors.